RUMAH MODE COSPLAY DI BANJARBARU - Noor, Matilda Adhistian; Rahman, Akbar; Febrita, Yuswinda (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
Kalimantan, among any other island in Indonesia, has one of the highest amount cosplay fans. Despite that, it’s still hard to find the material and even the costume itself in Banjarbaru, with the very limited amount of tailors that specialized in cosplay, to the fact that the price of a costume is way too high if bought from outside. Through the symbolic concept of “Konohagakure”, the design of Rumah Mode Cosplay in Banjarbaru was hoped to be a place for cosplay community and public it self, by giving a space for activity, education and recreation centered solely around cosplay. Sense of place was used to approach the feeling of being inside of an anime.